Faktor-Faktor Pendorong Petani Dalam Memilih Benih Kelapa Sawit (Elaeis guineensis) Bersertifikat Dan Nonsertifikat - Laura Juita Pinem; Mirna Pratiwi (Fakultas Pertanian, Universitas Timor, 2020)
Now, many palm oil farmers still use noncertified palm oil seed including farmer in Asahan District, North Sumatera. The use of noncertified palm oli seed causes big losses, its because productivity from noncertified palm oil seed smaller than certified palm oil seed. The purpose of the study was to identify the characteristics of farmer, analyze farmer decision and factors that determine farmer decision to utilize certified and noncertified oil palm seed in Asahan District, North Sumatera. This research use 100 farmer respondens. The method of the research is descriptive analysis and logistic regresion. The result showed that there were five major factors significantly influence the farmer’s decision to use certified and noncertified oil palm seed in Asahan District, there were age factor, resistance to pest and plant diseases factor, experience farming factor, scale of land area factor, and seed access factor.